Hypokalaemic paralysis revealing Sjögren syndrome in an elderly man. Issue 2 (1st February 1999) - al-Jubouri, M A; Jones, S; Macmillan, R; Harris, C; Griffiths, R D
Abstract : A 73 year old white man presented with life threatening hypokalaemic paralysis requiring admission to an intensive care unit. Biochemical investigations showed severe hypokalaemia with hyperchloraemic metabolic acidosis, a spot urine pH of 6.5, and a positive urinary anion gap, establishing the diagnosis of distal renal tubular acidosis. Autoimmune tests revealed Sjögren syndrome as the underlying cause of the distal renal tubular acidosis. Full recovery followed potassium and alkali replacement. This dramatic presentation of Sjögren syndrome has not previously been reported in an elderly man.